Characterization of multiple antilisterial peptides produced by sakacin P-producing Lactobacillus sakei subsp. sakei 2a - Gianni de Carvalho, Katia (2018)
Antimicrobial compounds produced by lactic acid bacteria can be explored as natural food biopreservatives. In a previous report, the main antimicrobial compounds produced by the Brazilian meat isolate Lactobacillus sakei subsp. sakei 2a, i.e., bacteriocin sakacin P and two ribosomal peptides (P2 and P3) active against Listeria monocytogenes, were described. In this study, we report the spectrum of activity, molecular mass, structural identity and mechanism of action of additional six antilisterial peptides produced by Lb. sakei 2a, detected in a 24 h-culture in MRS broth submitted to acid treatment (pH 1.5) and proper fractionation and purification steps for obtention of free and cell-bound proteins. The six peptides presented similarity to different ribosomal proteins of Lb. sakei subsp sakei 23K and the molecular masses varied from 4.6 to 11.0 kDa. All peptides were capable to increase the efflux of ATP and decrease the membrane potential in Listeria monocytogenes. The activity of a pool of the obtained antilisterial compounds [enriched active fraction (EAF)] against Listeria monocytogenes in a food model (meat gravy) during refrigerated storage (4 °C) for 10 days was also tested and results indicated that the populations of L. monocytogenes in the food model containing the acid extract remained lower than those at time 0-day, evidencing that the acid extract of a culture of Lb. sakei 2a is a good technological alternative for the control of growth of L. monocytogenes in foods.